Islam, Muslims, and America : understanding the basis of their conflict - Khan, Arshad (Algora Pub., 2003)
Islam, Muslims and America gives a sound introduction to the history of Islam's experiences with the West, and the principles of Islamic teachings; and in that context identifies and discusses the reasons for Muslim-West alienation. It highlights both the disconnect between true Islamic beliefs and extremist actions, and the failure of Americans to seek the root causes of the current anti-American trend. -- Publisher description.